The association between generalized anxiety disorder and disordered eating symptoms among Lebanese adults with the moderating effect of self esteem - Ralph Abdallah; Melyssa Assaf; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Sami El-Khatib; Feten Fekih-Romdhane; Souheil Hallit; Sahar Obeid (Scientific Reports)
Abstract Our study aims to assess the moderating effect of self-esteem in the association between generalized anxiety disorder and disordered eating symptoms among a sample of Lebanese adults. The study engaged a cohort of 629 participants, who were recruited in May 2023, utilizing a snowball sampling technique. Data were collected via a questionnaire that included socio-demographic variables and the following scales: the Generalized Anxiety Disorder Scale (GAD-5), the Eating Attitudes Test (EAT-7), and the Single Item Self-Esteem Scale (SISE). Higher GAD-5 scores (Beta = 0.01; p = .004) were significantly associated with higher EAT-7 scores. The interaction generalized anxiety disorder by self-esteem was also significantly associated with EAT-7 scores (Beta = − 0.003; p = .019), indicating that self-esteem moderates the relationship between GAD and disordered eating symptoms. At low (Beta = 0.006; p = .001) and moderate (Beta = 0.003; p = .007) levels of self-esteem, higher GAD-5 scores were significantly associated with higher EAT-7 scores (more severe disordered eating symptoms). In contrast, at high levels of self-esteem, the association was not significant (Beta = 0.001; p = .812), indicating that higher self-esteem may act as a protective factor, reducing the impact of GAD on disordered eating symptoms. While an association between anxiety and disordered eating symptomatology has been reported, this study adds to the body of literature by indicating that the strength of this association may vary with an individual’s level of self-esteem, which underscores the importance of integrating self-esteem-building strategies into therapeutic interventions aimed at reducing disordered eating in individuals facing anxiety. Future studies would allow for a more dynamic and nuanced understanding of the causal pathways between anxiety, self-esteem, and eating behaviors.